MANAJEMEN AKSESIBILITAS SARANA DAN PRASARANA BAGI PENYANDANG DISABILITAS DI MASJID KOTA SELONG LOMBOK TIMUR - Safitri, Asa Nur; Ahyar, Ahyar; Syaoki, Muhammad; Asa nur Safitri (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
Lombok is known by title as “Island of 1001 mosques”. Its existence on theone hand has given a better Islamic nuance. People with disabilities are those who have physical , intellectual or a combination of both limtations. On the other hand, the number of people with disabilities in East Lombok continues to increase every year. Selong is known to the public as the capital of East Lombok district, as the capital,it is only right. Selong is improving itself to improve facilities, infrastructure and buildings for the general public. Including people with disabilities. Considering that Lombok is a paradise for mosques and considering the large number of people with disabilities, mosques in the city of Selong are slowly starting to build mosque facilities that are friendly to the disabled. Hopefully in the future, the Selong City mosque will further imrove its facilities, especially for the disabled so that allworshipers can worship with facilities and services that are worth it.